(untitled) (KULT_online, 2009)
This bibliography by Hartmut Walravens not only offers a general review of Western research on printing and book-arts in imperial China, but also deals to some extent with the current state of research in Central Asia, Korea, and Japan. The author’s highly readable annotations which include brief abstracts and evaluations greatly enrich this benchmark work. The reference period extends to the year 2006 and covers a total of 2000 titles. While primarily intended for Western readers, with a majority of titles written in central European languages, the work does contain relevant literature from East Asia.